DIGITAL PAYMENT AND BRAND IMAGE INFLUENCE CONSUMERS' PURCHASING DECISIONS IN THE FOOD SECTOR - Amanda, Septiana; Widiya Avianti (Universitas Pasundan, 2024)
The central government has established the ITE Law No. 11 of 2008 on information and electronic transactions with the aim of improving trade and the national economy and improving public welfare. This is evidenced by the presence of several online payment programs or also known as digital payment applications that provide the ability to make non-cash payments through online transactions. The source of data in this study was obtained from the questionnaire (primary) distributed to the community in Mekargalih Village, Jatiluhur District, Purwakarta Regency. By sampling using non-probability sampling technique with purposive sampling method using slovin formula so that the sample obtained in this study as many as 291 respondents. In addition to ease of payment, another decision in the purchase of products on online shopping platforms is the brand image that affects the purchase intention of consumers. Complaints of payment through the ShopeePay application are perceived by consumers as an obstacle in purchasing, so this study was conducted to determine the effect of digital payments and brand image on purchasing decisions. Based on the results of research conducted, digital payment (X1) and brand image (X2) simultaneously affect the purchase decision. Based on the coefficient of determination test obtained the value of R square (R2) of 0.872. This value can be interpreted that digital payments and brand image are able to influence purchasing decisions by 87.2%.